The impact of topically applied preservation solutions on the respiratory epithelium of tracheal grafts submitted to cold ischemia: functional and morphological analysis (Clinics, 2013)
OBJECTIVE: Advances in graft reepithelialization and revascularization have renewed interest in airway transplantation. This study aims to determine whether topically applied preservation solutions can ameliorate ischemic injury to tracheal grafts. We analyzed 1) the effects of cold ischemia on the mucociliary clearance of tracheal grafts and 2) the impact of topically applied preservation solutions on the effects of cold ischemia on mucociliary clearance. METHOD: Tracheal segments (n=217) from 109 male Wistar rats were harvested, submerged in low-potassium-dextran-glucose, histidine-tryptophan-ketoglutarate, or saline solution (saline group), and stored at 4°C for 6, 10, 16, or 24 hours. A control group (not submerged) was analyzed immediately after harvesting. In situ mucociliary transport and ciliary beating frequency were measured using a stroboscope. Epithelial integrity, cellular infiltration, and mucus storage were quantified by light microscopy and image analysis software, along with transmission electron microscopy. RESULTS: 1) The effects of cold ischemia: in situ mucociliary transport and ciliary beating frequency were greater in the control group than after cold ischemia. Microscopic analysis results were similar between groups. 2) The effects of preservation solutions: there was no difference between the low-potassium-dextran-glucose, histidine-tryptophan-ketoglutarate, and saline groups in functional or light microscopy analysis. The saline group presented stronger signs of ischemic injury with transmission electron microscopy. CONCLUSIONS: Cold ischemia diminished the mucociliary clearance of the tracheal respiratory epithelium. Topically applied preservation solutions did not ameliorate the injury caused by cold ischemia to the tracheal respiratory epithelium.